Pembinaan Dan Penyelesaian Kredit Macet Pada Koperasi Simpan Pinjam Hari Sejahtera, Di Desa Bugbug, Kelurahan Bugbug, Kabupaten Karangasem - I Nyoman Budiartha; Ni Luh Made Mahendrawati; I Wayan Wesna Astara; Dessy Lina Oktaviani Suendra; Kade Richa Mulyawati; I Made Aditya Mantara Putra (Community Service Journal (CSJ), 2019)
Abstrak As one of the driving force of the middle economy, the cooperative has been growing rapidly in Indonesia in recent years. Bali Province is one of the best competition for Cooperative in Indonesia. This can be seen from the award given by the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia to the cooperatives in Bali. The government is also optimistic to continue to develop cooperatives in Bali well and right so that the future can meet the market both domestically and abroad, as well as the KOPWAN Mertasari, Karangasem District. This cooperative arises from the desire to develop a Dharma Wanita group within the Karangasem Regional Government in order to help the economy of the members even the Karangasem community. However, it is inevitable that various barrier factors are formed along with the establishment of this cooperative, one of which is bad credit. The problem of bad debts is the most common problem we encounter in banking institutions and it is very difficult to avoid. Therefore, in the course of a cooperative, it is necessary to prepare a variety of preparations to anticipate the occurrence of bad loans, one of them through a good credit analysis and the establishment of credit agreements with legal force